2020
DOI: 10.1097/md.0000000000020904
|View full text |Cite
|
Sign up to set email alerts
|

Microarray analysis of differentially expressed microRNAs in myelodysplastic syndromes

Abstract: Background: Our study aimed to analyze differential microRNA expression between myelodysplastic syndromes (MDS) and normal bone marrow, and to identify novel microRNAs relevant to MDS pathogenesis. Methods: MiRNA microarray analysis was used to profile microRNA expression levels in MDS and normal bone marrow. Quantitative real-time polymerase chain reaction was employed to verify differentially expressed microRNAs. Results: MiRNA microarray a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“… 21 In the course of MDS, miR-155-5p has been validated to present an up-trend expression level and is associated with high-risk MDS. 5 Furthermore, the increase of miR-155-5p has been also checked in the bone marrow of acquired aplastic anemia patients. 22 miR-155-5p concentration is elevated in the serum of AML patients and is feasible to distinguish AML patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 21 In the course of MDS, miR-155-5p has been validated to present an up-trend expression level and is associated with high-risk MDS. 5 Furthermore, the increase of miR-155-5p has been also checked in the bone marrow of acquired aplastic anemia patients. 22 miR-155-5p concentration is elevated in the serum of AML patients and is feasible to distinguish AML patients.…”
Section: Discussionmentioning
confidence: 99%
“…It is underlined that miRNAs with differential expression may represent pathogenic implications of MDS in part by regulating hematopoiesis, and miR-155-5p is an upregulated miRNA in MDS. 5 More importantly, miR-155 transcript maintains a high level in CD34 + MDS cells 6 and miR-155 can decrease RAC1 protein to regulate MDS neutrophils migration. 7 RAC1, a member of the Rho GTPases family, functions in various hematopoietic cell lineages 8 and RAC1 activation promotes human hematopoietic stem and progenitor cell maintenance.…”
Section: Introductionmentioning
confidence: 99%
“…Target loss with rs4695253 was predicted for six miRNAs: MiR-1264 was upregulated in the circulation 3 h after ischemia ( 51 ) and critical limb ischemia in T2DM ( 52 ), and downregulated in neuroglioma ( 53 ). MiR-550a-3p was downregulated in myelodysplastic syndromes ( 54 ). MiR-550a-3p also plays its tumor-suppressor role by directly repressing ERK1 and ERK2 protein expression, thereby suppressing the oncogenic ERK/RSK cascade to reduce breast cancer cell viability, survival, migration, invasion, tumorigenesis, and metastasis ( 55 ).…”
Section: Discussionmentioning
confidence: 99%
“…miR-550a-3p can negatively regulate the expression of ERK1 and ERK2. 13 Upregulation of miR-550a-3p in sarcopenia may lead to the downregulation of the ERK1/2 signaling pathway. A previous study showed that Hachimijiogan promoted the proliferation of C2C12 skeletal muscle cells through the ERK1/2 signaling pathway without activation of the Akt signaling pathway.…”
Section: Discussionmentioning
confidence: 99%